The association between catechol o-methyltransferase (comt) rs4680 polymorphism, harm avoidance scores, and concussion history in rugby union players. Issue 11 (25th May 2017) - Fie, Sarah MC; Abrahams, Shameemah; Patricios, Jon; Suter, Jason; Posthumus, Michael; September, Alison V
Abstract : Objective: To investigate the relationship between personality traits and Catechol O-methyltransferase (COMT) rs4680 genotypewith concussion history in rugby players. Design: Case-control study. Setting: High school, amateur, and professional rugby teams in South Africa. Participants: Participants were excluded if they reported a previous brain-related medical condition or a non rugby-related concussion, or were not of European ancestry. Three hundred and one participants were included in the study. Based on self-reported concussion history (30 suspected concussion cases were excluded), participants were grouped into the control (non-concussed, n=140) or case group (one or more diagnosed concussions, n=131). Assessment of risk factors: Participants completed a concussion history questionnaire, Cloninger's Tridimensional Personality Questionnaire (TPQ) and all DNA samples were genotyped for COMT rs4680. Logistic regression, co-varying for age, was used to determine differences in genotype frequencies. A one-way analysis of variance was used to compare TPQ dimension (novelty seeking, harm avoidance, and reward dependence) scores. Outcome measures: COMT rs4680 genotype frequencies and TPQ scores. Main results: The COMT rs4680 VV genotype was overrepresented in the controlgroup when all participants were combined (p=0.030, OR: 1.89, 95% CI: 1.05 – 3.45; control: 31%, cases: 18%) and whenonly school participants were analysed (p=0.009, OR: 3.23, 95% CI: 1.27 – 8.33; control:37%, cases:15%). Furthermore, the schoolcontrol group had higher harm avoidance scores compared to cases (p=0.004), andthe VV genotype was associated with increased harm avoidance subscale 1 scores (p=0.023). Conclusions: This study provides preliminary indication that personality traits, and associated genetic variants, can influence concussion in rugby. Competing interests: None.